Prognostic predictions based on pathological findings of peritoneal dissemination in patients with stage IV colorectal cancer without residual disease (R0 status) - Komori, Koji; Kinoshita, Takashi; Oshiro, Taihei; Ouchi, Akira; Ito, Seiji; Abe, Tetsuya; Senda, Yoshiki; Misawa, Kazunari; Ito, Yuichi; Natsume, Seiji; Higaki, Eiji; Okuno, Masataka; et al. (Surgery today (Tokyo, Japan), 2019)
Purpose This study aimed to clarify the prognosis of patients after resection of stage IV colorectal cancer and synchronous peritoneal metastasis (no residual disease: R0 status) based on histopathologic findings. Methods The subjects of this study were 26 patients who underwent radical resection of synchronous peritoneal metastases of stage IV colorectal cancer. Only patients with one synchronous peritoneal metastasis were included in this study. The peritoneal lesions were initially classified into two categories based on the presence or absence of adenocarcinoma on their surface: RM-negative or RM-positive. The lesions were subsequently classified as being of massive or diffuse type and of small (< 6 mm) or large (≥ 6 mm) type according to the maximum metastatic tumor dimension. Results Multivariate analysis revealed that massive type metastatic tumors were associated with a better disease-free survival (DFS; p = 0.047) and overall survival (OS; p = 0.033), than diffuse type tumors. Conclusion A detailed stratification of pathological findings could contribute remarkably to prognostic predictions for patients with synchronous peritoneal metastases.